STREOTIPE GENDER DAN PILIHAN KAREER DI KALANGAN SISWI MADRASAH ALIYAH (MA) DINIYAH PUTERI PEKANBARU RIAU - Riswani -; Hermansyah - (Marwah: Jurnal Perempuan, Agama dan Jender, 2015)
This study is a descriptive research in the form of a survey of 50 female students of Madrasah Aliyah. It disclosed is whether the students know that men and women can not be distinguished by the characters and roles, career what they would choose if already left school and what form career guidance given by the counseling teacher to reduce the attitude of gender stereotypes in students career choices. The results showed students know that men and women can not be distinguished by the character and role. Then, there are students who choose a job that is considered masculine and feminine as a future career. Student knows that men and women can not be distinguished by the character and role when they received material about gender in career information services provided by counseling teacher. The researchers concluded that gender stereotypes in students career choices can be minimized through the perspective of career guidance services. Researchers suggest there should be a gender perspective in the training of career guidance in Islamic schools.